Chemiluminescence determination of human serum albumin based on Co2+-catalyzed 2-(4-tert-butylphenyl)-4, 5-di(2-furyl) imidazole/H2O2 system. Issue 109 (20th October 2015) - Kang, Jing; Shen, Jimin; Chen, Zhonglin; Nan, Jun; Huang, Xiao; Han, Lu; Hao, Weiping
Abstract : Co 2+ could effectively enhance the sensitivity of the 2-(4- tert -butylphenyl)-4, 5-di(2-furyl) imidazole/H2 O2 chemiluminescence reaction. Abstract : In this paper, the chemiluminescence (CL) reaction of 2-(4- tert -butylphenyl)-4, 5-di(2-furyl) imidazole ( t -BDFI) and H2 O2 was investigated in alkaline medium. The H2 O2 could directly oxidize t -BDFI to produce CL emission. The effects of some metal ions on CL of the t -BDFI/H2 O2 system were examined. The results indicated that the addition of Co 2+ into the t -BDFI/H2 O2 CL system could induce significant enhancement of the CL signal. A CL system of t -BDFI/H2 O2 /Co 2+ was developed. The experiment on the effect of human serum albumin (HSA) on the t -BDFI/H2 O2 /Co 2+ CL system was carried out, and the result indicated that HSA could effectively inhibit the CL signal of this reaction. The inhibited CL intensity is linearly related to the logarithm of concentration of HSA. The linear range of the calibration curve is 5.0 × 10 −8 to 1.0 × 10 −6 mol L −1, and the corresponding detection limit (3 σ ) is 2.1 × 10 −8 mol L −1 . Based on this study, a novel CL method has been developed for the determination of HSA with high sensitivity and good selectivity. The proposed method has been successfully applied to the determination of HSA in human serum samples. This may intrigue researchers into gaining a new interest in investigating the CL property of heterocyclic imidazole derivatives.